Definition of area and center of technological safety in space of conditions of the production system - R. Bakasov, S; E. Prorokov, A; N. Matveev, Yu.; N. Bogatikov, V; V. Palux, B (International Journal of Engineering and Technology, 2018)
Abstract. Realization of system of diagnostics of states and management of technological safety in space of states is considered. The technique of definition of the center of safety on the basis of the solution of a problem of linear programming and the two-level system of decision-making on ensuring technological safety is offered. At the first level the center of safety is defined, at the second level the problem of stabilization of process in the field of safe functioning is solved.